A STUDY OF NHA TRANG BAY MARINE PROTECTED AREA’S MANAGEMENT EFFECTIVENESS - Anh, Nguyen Thi Kim; Khanh, Tran (Vietnam Journal of Marine Science and Technology, 2009)
The Nha Trang Bay Marine Protected Area (MPA) was established since 2002. Its objective is “To protect marine biodiversity environment and to enable local island communities  to  improve their  livelihoods  and  in  partnership  with  other  stakeholders  to effectively  protect  and  manage  the  marine  biodiversity  in  Nha Trang  Bay  as  a  model  for collaborative MPA management in Vietnam.” After a period of operating, to consider whether the  Nha Trang  Bay  MPA  achieves  the  objectives,  a  study  of  Nha  Trang bay  MPA’s management effectiveness has been developed. With the associating of 3 study methods: taking expert advice, social survey and descriptive statistics, the authors have investgated 4 island villages:  Bich  Dam,  Vung  Ngan,  Hon  Mot  and  Dam  Bay through  face  to  face  and  deep interviews  in  the  end  of 2008. The  results  show  that  with  the  objective  to  protect  marine biodiversity, the MPA has been done well. However, the other objective to enable local island communities to improve their livelihoods has fallen short of its expectations.